2014
DOI: 10.1037/a0038037
|View full text |Cite
|
Sign up to set email alerts
|

Motor impulsivity during childhood and adolescence: A longitudinal biometric analysis of the go/no-go task in 9- to 18-year-old twins.

Abstract: In the present study, we investigated genetic and environmental effects on motor impulsivity from childhood to late adolescence using a longitudinal sample of twins from ages 9 to 18 years. Motor impulsivity was assessed using errors of commission (no-go errors) in a visual go/no-go task at 4 time points: ages 9–10, 11–13, 14–15, and 16–18 years. Significant genetic and nonshared environmental effects on motor impulsivity were found at each of the 4 waves of assessment with genetic factors explaining 22%–41% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 43 publications
1
29
0
2
Order By: Relevance
“…While environmental influences contributed modestly to some of the within-time associations among depression, conduct, and hyperactivity symptoms, these common environmental influences were time specific and did not contribute to the symptom co-occurrence over time. Instead, we found that shared and non-shared environmental influences contributed only to the homotypic continuity of depression and hyperactivity, respectively, in line with previous findings from early to middle adolescence [65,66]. Most notably, majority of non-shared environmental influences were time and symptom specific, contributing to symptom discontinuity over time.…”
Section: Discussionsupporting
confidence: 90%
“…While environmental influences contributed modestly to some of the within-time associations among depression, conduct, and hyperactivity symptoms, these common environmental influences were time specific and did not contribute to the symptom co-occurrence over time. Instead, we found that shared and non-shared environmental influences contributed only to the homotypic continuity of depression and hyperactivity, respectively, in line with previous findings from early to middle adolescence [65,66]. Most notably, majority of non-shared environmental influences were time and symptom specific, contributing to symptom discontinuity over time.…”
Section: Discussionsupporting
confidence: 90%
“…Two independent, but complimentary lines of inquiry may provide insights into possible mechanisms of these developmental differences. First, developmental theories emphasize reductions in impulsivity over adolescence, which are linked to the protracted development of prefrontal regions over the same developmental period (Bezdjian et al, 2014;Brookman-Byrne, Mareschal, Tolmie, & Dumontheil, 2018;Hallquist, Geier, & Luna, 2018;Steinberg et al, 2017). Second, computational theories of speed-accuracy trade-offs highlight that the time to arrive at a cognitive solution gives insights into the amount of evidence participants sample before deciding upon a solution (Fitts, 1966;Stone, 1960 tests, which have been used for decades, also arguably carry a higher likelihood of familiarity than novel items like MaRs-IB.…”
Section: Discussionmentioning
confidence: 99%
“…These changes in reasoning performance during development have been linked to the protracted maturation of the frontal cortex (Bazargani, Hillebrandt, Christoff, & Dumontheil, 2014;Crone et al, 2009;Dumontheil, Houlton, Christoff, & Blakemore, 2010). During the same developmental period, impulsivity decreases markedly (Bezdjian, Tuvblad, Wang, Raine, & Baker, 2014;Steinberg et al, 2017), raising the possibility that increases in reasoning scores could reflect either true increases in reasoning capacity, a decrease in impulsivity, or both. In other words, there may be a developmental speed-accuracy trade-off.…”
Section: Introductionmentioning
confidence: 99%
“…IC was measured using no-go accuracy (Bezdjian, Tuvblad, Wang, Raine, & Baker, 2014). The present task was administered via E-Prime 2.0 (Psychology Software Tools, Inc., Sharpsburg, PA), and it includes 20 practice trials (10 go trials and 10 no-go trials) and 160 test trials in random order.…”
Section: Inhibitory Controlmentioning
confidence: 99%